The assessment of Qur’an reciting competitions using the fuzzy evaluation method / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Mohd Idris, Mohd Fazril Izhar; Wan Daud, Wan Suhana; Tajaludin, Abdul Muhaimin (Universiti Teknologi MARA, Perlis, 2022)
A Qur’an Reciting Competition evaluates a participant's performance based on several factors, including Tajweed, Tarannum, Fasohah, and Vocal Quality. Participants in the Qur’an Reciting Competition are usually assigned a point value of 100, with each point representing a linguistic word or label such as “Exceptional,” “Excellent,” “Fairly Good,” and so on. Evaluating participant performance seems difficult because it involves human decision-making, which is imprecise, ambiguous, and unpredictable. This study employed the fuzzy evaluation method to assess participants’ performance at a Qur’an Reciting Competition in Klang. In this manner, the membership function graph was used to determine the membership value of each satisfaction level. The satisfaction level of each participant’s mark was then computed. At the end, the fuzzy markings with linguistic values would be obtained. The proposed method provides an alternative approach that is reasonable and intelligent in assessing competitors’ performance. This method is practical because it can increase the satisfaction of participants and assist the panels in making more reliable decisions during the competition.